Understanding Hadith Delay Time Prayer Midday Prayer on Moment Scorching Heat - Nurul Jannah; Nurlizam Nurlizam (Institut Agama Islam Sumatera Barat, 2024)
When performing prayers, Muslims are commanded to keep the prayer with the virtue of performing it at the beginning of time. Zuhr prayer time begins when the sun is just above the head and slightly inclined to the west. However, the Prophet Muhammad once ordered to postpone the Zuhr prayer because of the heat. The purpose of this study is to determine the understanding and contextualization of the hadith about delaying the Zuhr prayer time in the heat of the day. It is expected to bring benefits to provide knowledge and understanding of the hadith so that it can be contextualized according to the current situation. This research uses a qualitative method with library research. In addition, this research is in the form of the hadith analysis method with the aim of exploring the content of the hadith in depth. The understanding of the hadith is done by examining the textual and contextual of the hadith. The result of this study is that the hadith is a recommendation. The delivery of the hadith was motivated by the situation of the Prophet Muhammad SAW traveling with his companions and the weather temperature in the region greatly affected the delivery of the hadith. Then the situation at that time there were not many buildings and mosques as a shelter from the heat of the sun. Contextualisation of the Hadith in today's era that has progressed so that there are air conditioners and many buildings and mosques as a shelter making the scorching heat should no longer be used as an excuse to delay the Zuhr prayer time. So it is more advisable to take the virtue of performing the Zuhr prayer at the beginning of time.